Intraosseous Lipoma of the Sphenoid: A Case Study. (28th May 2013) - Jamrozik, Zygmunt; Rosiak, Grzegorz; Kierdaszuk, Biruta; Milczarek, Krzysztof; Kamińska, Anna; Dziewulska, Dorota; Krzeski, Antoni
Abstract : Intraosseous lipoma is very rare, usually benign tumor of flat bones. However, the localization in skull bones is described in sporadic cases. The differential diagnosis includes end stage of infection, infarct lesions, intraosseous meningioma, angiolipoma, or myxofibrous tumors. We report a patient with intraosseous lipoma located in the sphenoid bone. The diagnosis was established due to the characteristic radiological features. According to the history of seizures, the lesion was removed via endoscopic endonasal approach. Histopathological examination showed adipocytes. The patient underwent control neuroimaging studies.